Growth and Yield of Soybean with Application of Liquid Organic Fertilizer and Arbuscular Mycorrhizal Fungi in Ultisols - Lisa Septiani; RR Yudhy Harini Bertham; Hesti Pujiwati; Bilman Wilman Simanihuruk (TERRA : Journal of Land Restoration, 2021)
Soybean (Glycine max (L.) Merill) is the third most important food crop after rice and corn which contains protein and other nutrients essential for the body. Ultisol soil is a less fertile soil that has many limitations on its physical, chemical, and biological properties. Efforts that can be made include the use of liquid organic fertilizer (LOF) and arbuscular mycorrhizal fungi (AMF). This research was conducted from February to May 2020, in Beringin Raya, Muara Bangka Hulu District, Bengkulu City with an altitude of + 10 m above sea level. The purpose of this study was to explain the growth and yield of soybeans due to the application of liquid organic fertilizers and arbuscular mycorrhizal fungi in Ultisols. The research design used was a randomized complete block design (RCBD) with 2 factors with three replications. The first factor is the LOF dose which consists of four levels, namely: 0, 20, 40, and 60 mL L-1. The second factor is the AMF dose with three levels, namely; 0, 5, and 10 g plant-1. The results showed that there was no interaction between LOF and AMF. Giving a LOF concentration of 60 mL L-1 gave the highest yield on the growth and yield of soybeans, as well as the optimum concentration for seed/plant weight, which was 28.114 mL L-1, and the number of seeds was 37.589 mL L-1. AMF dosage of 10 g plant-1 gave the best growth and yield of soybean plants.